INSTITUTIONAL APPROACH TO ACCOUNTING AND FINANCIAL REPORTING: NECESSITY AND POSSIBILITY OF ITS APPLICATION AT PRESENT STAGE OF SCIENCE DEVELOPMENT - O. A. Ageeva (Вестник университета, 2019)
The general science genesis as well as particularly accounting science genesis, in search of contemporary approaches towards identification of new problems, arising at current science development stage, and methods to ensure its solution has been considered. The conclusion has been made, that the most actual although the least studied is institutional approach to accounting and financial reporting development. Institutional aspects of accounting and financial reporting have been generalized, сurrent main directions of research in the field of accounting and financial reporting have been revealed, the development of which is possible on the basis of an institutional approach.